ANALISIS PERTIMBANGAN HUKUM PENETAPAN PERKARA NO. 155/PDT.P/2023/ PN.JKT.PST TENTANG PERKAWINAN BEDA AGAMA - NIM. A1011181163, IHZA RIANSA (Jurnal Fatwa Hukum, 2024)
AbstractThe judge's legal consideration regarding the registration of interfaith marriages according to Indonesian positive law is Article 35 letter (a) of Law Number 23 of 2006 concerning Population Administration which reads: "Marriages determined by the Court". So the District Court in Decision Number 155/PDT.P/2023/PN.JKT.PST decided to give permission to Joshua Evan Anthony and Stefany Wulandari to carry out registration of interfaith marriages at the Central Jakarta City Population and Civil Registration Sub-department Office by showing a copy. determination that already has permanent legal force.The method used in this research is a normative method. Normative legal research is legal research on secondary data in the form of library research which is carried out by examining library materials in the form of primary, secondary and tertiary data.The results of the analysis from this research are that the judge's considerations in granting permission to register interfaith marriages in the determination of case Number 155/PDT.P/2023/PN.JKT with the issuance of SEMA Number 2 of 2023 were addressed to the Chairman/Head of the High Court of Appeal and the Chairman /The Head of the Court of First Instance expects all Judges to comply with the rules so that the decision in case Number 155/PDT.P/2023/PN.JKT is annulled by the Supreme Court and the marriage between the two parties is declared legally invalid.Keywords: Legal Considerations, Marriage, Different ReligionsAbstrakPertimbangan hukum hakim terhadap pencatatan perkawinan beda agama menurut hukum positif Indonesia ialah Pasal 35 huruf (a) Undang-Undang Nomor 23 Tahun 2006 tentang Administrasi Kependudukan yang berbunyi: "Perkawinan yang ditetapkan oleh Pengadilan". Jadi Pengadilan Negeri dalam Putusan Nomor 155/PDT.P/2023/PN.JKT.PST menetapkan dengan memberikan izin kepada Joshua Evan Anthony dan Stefany Wulandari untuk melangsungkan pencatatan perkawinan beda agama di Kantor Suku Dinas kependudukan dan Pencatatan Sipil Kota Jakarta Pusat dengan menunjukkan salinan penetapan yang sudah mempunyai kekuatan hukum tetap.Metode yang digunakan dalam penelitian ini adalah metode normatif. Penelitian hukum normatif adalah penelitian hukum terhadap data sekunder berupa penelitian kepustakaan (library research) yang dilakukan dengan cara meneliti bahan kepustakaan yang berupa data primer, sekunder, dan tersier.Hasil analisis dari penelitian tersebut adalah \Bahwa pertimbangan hakim dalam memberikan izin pencatatan perkawinan beda agama dalam penetapan perkara Nomor 155/PDT.P/2023/PN.JKT dengan dikeluarkanya SEMA Nomor 2 Tahun 2023 yang ditujukan kepada Ketua/Kepala Pengadilan Tinggi Banding dan Ketua/Kepala Pengadilan Tingkat Pertama diharapkan semua Hakim untuk tunduk pada aturan sehingga penetapan perkara Nomor 155/PDT.P/2023/PN.JKT dibatalkan oleh Mahkamah agung dan perkawinan antara kedua pihak tersebut dinyatakan tidak sah secara hukum.    Kata Kunci : Pertimbangan Hukum, Perkawinan, Beda Agama